Adrenal Ganglioneuromas: Experience from a Retrospective Study in a Chinese Population - Li, Liping; Shao, Jialiang; Gu, Jianjun; Wang, Xiang; Qu, Lianxi (Urology Journal, 2014)
Abstract Purpose: Ganglioneuromas (GNs) are benign neoplasms of combined neural crest, schwannian,and connective tissue origin, occurring rarely in the adrenal glands. The present study isto share our experience regarding diagnostic and therapeutic management of these tumors. Materials and Methods: Adrenal GNs of 15 patients were found incidentally with ultrasonographyand were evaluated subsequently with computed tomography (CT) scan. Clinical dataas well as follow-up data were collected retrospectively. All the patients received operativeresection. Results: The mean age of the patients was 38.4 years (range, 25-52 years; male to female ratio,2:1). Of study subjects 11 patients had unilateral GN on the right side, and the remaining4 on the left side. All but 1 patient were asymptomatic. No hormonal secretion was apparent.Mean size of the tumors in CT scan was 6.27 cm (range, 2.5-14 cm), while 10 were largerthan 5 cm. Eight patients underwent open adrenalectomy and the remaining 7 underwentlaparoscopic anterior adrenalectomy. Histologically, all 15 neoplasms were completely differentiated,mature GN. We had no mortality or significant morbidity. Mean duration of hospitalization was 5.5 days (range, 3-7 days). There was no recurrence, during a mean followupof 5.4 years (range, 1-10 years). Conclusion: Pre-operative diagnosis of adrenal GNs remains difficult merely according tophysical examination. Therefore, we recommend complete operative resection once malignancycannot be excluded by pre-operative analyses. Laparoscopic adrenalectomy is a reasonableoption, at least for tumors ≤ 5 cm.